2014
DOI: 10.9790/3021-04411523
|View full text |Cite
|
Sign up to set email alerts
|

Influence of continuous plastic fibers reinforcement arrangement in concrete strengthened

Abstract: Many studies have been done using waste short plastic fibers to reinforce concrete. The objective of this investigation is the development of a novel arrangement of reinforcement with continuous recycled PET fibers, to enhance the mechanical properties of concrete beams. The novel arrangement consists of continuous PET fibers of the same length as concrete beams, placed in the mold, fixed and prestressed prior to casting the concrete. Due to the fact that in previous investigations on concrete reinforced with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
0
10
1
Order By: Relevance
“…e most effective technique of mitigating concrete cracking is by reinforcing shotcrete with fibers. Randomly distributed fibers in concrete provide bridging forces across cracks and thus improve the concrete strength [9][10][11][12]. So far, different types of fibers have been used in reinforced concrete.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…e most effective technique of mitigating concrete cracking is by reinforcing shotcrete with fibers. Randomly distributed fibers in concrete provide bridging forces across cracks and thus improve the concrete strength [9][10][11][12]. So far, different types of fibers have been used in reinforced concrete.…”
Section: Introductionmentioning
confidence: 99%
“…ere are two methods for producing the PET fiber. One way is to cut a PET bottle by hand or using a mechanical cutting device [11,13,19]; the other is to melt the PET bottle and then pull them into monofilaments by an extruder [15,[20][21][22][23]. e properties of PET fiber, such as physical, chemical, and mechanical features, affect the concrete reinforcement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the bottles were cut by hand or a mechanical cutting device, as reported in the literature [48,49], which is simplest and economic cutting method. The fiber dimensions were approximately 2-3 mm in width, 0.34 mm in thickness and lengths of 20-25 mm for fibers ( Figure 3).…”
Section: Fibersmentioning
confidence: 99%
“…Different waste bottles (such as refreshing drinks, water, tea and juices) were measured [48,49]. The results showed that all the PET fiber samples basically had the same spectrum according to FTIR spectra tests, slight differences of crystallinity observed by tests of DSC (differential scanning calorimetry) thermograms, the Young's modulus and tensile strength of 3830 ± 47 MPa, 108 ± 15 MPa, respectively [48,49]. Thus, different waste bottles had a minor variation from one sample to another.…”
Section: Fibersmentioning
confidence: 99%